Efficacy of Transanal Drainage Tube Placement After Modified Posterior Pelvic Exenteration for Primary Ovarian Cancer. Issue 2 (1st February 2018) - Kato, Kazuyoshi; Omatsu, Kohei; Matoda, Maki; Nomura, Hidetaka; Okamoto, Sanshiro; Kanao, Hiroyuki; Utsugi, Kuniko; Takeshima, Nobuhiro
Abstract : Objective: The aim of this study was to investigate the clinical usefulness of the placement of a transanal drainage tube (TDT) to prevent anastomotic leakage after a modified posterior pelvic exenteration (MPPE) for the treatment of primary ovarian cancer. Methods: We performed a retrospective review of all the consecutive patients who had undergone an MPPE for primary ovarian, tubal, or peritoneal cancer between October 2012 and November 2016 at our institution. Patient-related, disease-related, and surgery-related data were collected. Results: One hundred five patients who underwent an MPPE were included in this study. A TDT was placed in all the patients. A diverting ileostomy was created during cytoreductive surgery in 7 patients (7%). Those who underwent a diverting ileostomy tended to have a greater degree of surgical invasiveness, as was reflected by a longer operative time, a serious loss of blood, and a large quantity of intraoperative blood transfusion. Anastomotic leakage occurred in 1 patient (1%), and a diverting ileostomy was created for this patient. Conclusions: Transanal drainage tube placement seems to be an effective and safe procedure that can decrease the rate of anastomotic leakage and the need for a diverting stoma after MPPE for ovarian cancer. However, some patients inevitably require a diverting stoma despite the TDT placement.